Efeito de intervenção com realidade virtual sobre a condição de saúde de crianças com paralisia cerebral - Arnoni, Joice Luiza Bruno (Universidade Federal de São Carlos, 2015)
Virtual reality (VR) has been considered an important tool for rehabilitation of children with cerebral palsy (CP). Nevertheless, although there is some evidence about its positive effects in rehabilitation by means of existent systematic reviews, its important to investigate the methodological quality of these reviews, providing an update and also enabling practice based on evidence. Thus we developed the Study 1, with the objective of synthetize in a descriptive way the results of the existent studies and evaluate the methodological quality of the existent systematic reviews which employed VR as a tool in the rehabilitation of children with CP. The results of this first study allow us to identify the lack of primary studies in the evaluated reviews presenting a good level of evidence as well as an adequate methodological design. Moreover, the use of reliable outcome measures such as the quantitative measure of postural oscillation by means of force plate and validated scales and questionnaires might help in a reliable investigation of the effects of VR in rehabilitation of CP children. Thus, taking into account the lack of studies with good levels of evidence about the effects of the use of VR in rehabilitation, we developed the Study 2 with the aim of evaluate the effects of an intervention using VR in children with CP on their levels of postural oscillation, gross motor function and assiduousness to the therapy. Methods: In the Study 1 we searched the databases PubMed, Science Direct, Web of Science, Scopus, Lilacs, Scielo, PEDro and Cochrane Database of Systematic Reviews using the following keywords: child, children, virtual reality , videogame system and cerebral palsy . We selected 5 studies which meet the inclusion criteria and evaluated it using the Overview Quality Assessment Questionnaire. Study 2 was a randomized controlled trial with longitudinal design and clinical purposes. Fifteen children with CP (10±3 years) with levels I and II of Gross Motor Function Classification System (GMFCS), regularly inserted in physical therapy programs participated in the study. We did not include children with deficits that could compromise their performance in the proposed activities in virtual environment. The sample was shared in two groups by chance: Intervention Group (IG=7) and Control Group (CG=8). GI was submitted to a VR intervention protocol using an active videogame (Xbox 360º Kinect) which lasted 8 weeks with 45 sessions twice a week. CG was instructed to keep their traditional rehabilitation activities. We used four games with demands of balance, motor coordination, jumps, squats and latero-lateral weight shifts. All the children were evaluated in the beginning and after the end of the intervention protocol using the force platform and the Gross Motor Function Measure (GMFM) in the dimensions D and E. The analyzed variables in force platform were total oscillation of the center of pressure (TO of CoP), medio-lateral and antero-posterior amplitude of CoP displacement (ML and AP Amp of CoP), area and velocity of CoP oscillation (Vel of CoP). We calculated the clinically significant changes in GMFM (> 1%) and assiduousness to the therapy. Statistical analysis was conducted using MANOVA with repeated measures to verify differences between the groups before and after the intervention protocol to postural oscillation and Wilcoxon test to verify differences between before and after the intervention to variables of GMFM. Results: Study 1: Primary studies of the reviews were published between 1995 and 2011. The most used databases were CINAHL, EMBASE e PEDro. The most used instrument to evaluate quality of the reviews was American Academy for Cerebral Palsy and Developmental Medicine. The main used equipment was Mandala Gesture XTreme e Rehabilitation Exercise System. The quality assessment of the reviews have showed one study with minimums methodological failures, three studies with small ones and one paper presented small defects. Study 2: We observed a significant difference pre and post intervention. We only verified clinically significant changes in the dimensions D and E of GMFM for the IG. All participants in GI completed the eight weeks of intervention with an assiduousness of 85,1% ±8,7%. We did not find significant differences for the force platform variables related to postural oscillation. Conclusions: Study 1: VR has been widely employed in the rehabilitation of children with CP. We identified a growing trend in the interest for this issue in literature. Although we have found systematic reviews with good methodological quality, the level of evidence of the primary studies was low. Study 2: Rehabilitation using VR by means of videogame was able to improve gross motor function in children with CP levels I and II of GMFCS and also keep high levels of assiduousness to therapy. However, we could not find similar results in the patterns of postural oscillation. These results enable us to use VR as an adjuvant therapy in physical rehabilitation of children with CP.
Keywords: Paralisia cerebral; Crianças; Realidade virtual; Video games; Prática baseada em evidências; Reabilitação; Children; Virtual reality; Videogame; Cerebral palsy; Rehabilitation; Evidence practice based; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL